Joint constraints on thermal relic dark matter from strong gravitational lensing, the Ly α forest, and Milky Way satellites - Enzi, Wolfgang; Murgia, Riccardo; Newton, Oliver; Vegetti, Simona; Frenk, Carlos; Viel, Matteo; Cautun, Marius; Fassnacht, Christopher D; Auger, Matt; Despali, Giulia; McKean, John; Koopmans, Léon V E; et al. (Monthly notices of the Royal Astronomical Society, 2021)
We derive joint constraints on the warm dark matter (WDM) half-mode scale by combining the analyses of a selection of astrophysical probes: strong gravitational lensing with extended sources, the Ly α forest, and the number of luminous satellites in the Milky Way. We derive an upper limit of λhm = 0.089 Mpc h−1 at the 95 per cent confidence level, which we show to be stable for a broad range of prior choices. Assuming a Planck cosmology and that WDM particles are thermal relics, this corresponds to an upper limit on the half-mode mass of Mhm < 3 × 107 M⊙ h−1, and a lower limit on the particle mass of mth > 6.048 keV, both at the 95 per cent confidence level. We find that models with λhm > 0.223 Mpc h−1 (corresponding to mth > 2.552 keV and Mhm < 4.8 × 108 M⊙ h−1) are ruled out with respect to the maximum likelihood model by a factor ≤1/20. For lepton asymmetries L6 > 10, we rule out the 7.1 keV sterile neutrino dark matter model, which presents a possible explanation to the unidentified 3.55 keV line in the Milky Way and clusters of galaxies. The inferred 95 percentiles suggest that we further rule out the ETHOS-4 model of self-interacting DM. Our results highlight the importance of extending the current constraints to lower half-mode scales. We address important sources of systematic errors and provide prospects for how the constraints of these probes can be improved upon in the future.